PENGARUH SHOPPING ORIENTATION, SOCIAL INFLUENCE, DAN SYSTEM TERHADAP COSTUMER ATTITUDE MELALUI PERCEIVED EASE of USE (Studi pada Apple Store) - Steven Haryono (Jurnal Strategi Pemasaran, 2015)
App store is a product of Apple Inc. who has been managing the website as well as other critical components in the online business. The service lets users browse the App store and download a variety of applications that have been developed by Apple. Therefore, to continue to develop the App Store need to know the factors that may affect attitudes of consumers like shopping orientation, social influence and the system through customer attitude and perceive ease of use. By knowing these factors, the App Store can find out how consumer attitudes on applications in the App store offer. In addition, the App Store also need to know how strong the influence of these factors on consumer attitudes.This study aims to analyze the influence of shopping orientation, social influence, and the system to the customer attitude in purchasing online App Store. In addition, to analyze the effect of perceived ease of use to the customer attitude towards purchasing online App Store.This study will be conducted by distributing questionnaires to 100 respondents purchaser applications in the App Store. Analysis technique used is the technique of quantitative analysis methods Equaiton Structural Modeling (SEM) with the help of the program Partial Least Square (PLS).These results indicate that perceive ease of use use significant positive effect on customer attitude, shopping orientation, social influence and the system significant positive effect on perceived ease of use.